KESULIATAN YANG DIHADAPI OLEH GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR PEKANBARU - Innaya Meidini Sastri; Yuni Ariesty; M Jaya Adiputra; Mauliatun Nisa (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to identify the challenges faced by teachers in implementing the Merdeka Curriculum in elementary schools in Pekanbaru. The Merdeka Curriculum is an educational innovation focused on differentiated learning and character development aligned with the Pancasila Student Profile. Although this curriculum offers flexibility and freedom in the learning process, teachers still face various challenges in understanding and applying it in the classroom. A qualitative method was used in this study by collecting data through surveys and interviews. The results of the study show that while some teachers understand the basic concepts of the Merdeka Curriculum, difficulties remain in developing learning materials, grasping new concepts, and dealing with limited resources and time. Support from schools and the education department, especially in the form of continuous training and adequate facilities, is essential to ensure the successful implementation of the Merdeka Curriculum.